The Costs of Charging Electric Vehicles in Poland - Sendek-Matysiak, Ewelina; Rzędowski, Hubert (Communications - Scientific Letters of the University of Zilina, 2022)
The very important factor that influences the decision of those interested in buying a vehicle is its operating costs. This paper determines the costs of driving 100 km for various electric vehicles, charging service providers and chargers, which was then confronted with the costs of refueling. Based on the analysis carried out, it was determined that, at present, the lowest costs of fueling/charging of a vehicle in Poland are connected with use of an electric vehicle, but only when the charging is performed with use of public AC chargers. Moreover, it was determined that the savings that will result from charging electric vehicles at AC charging stations as compared to filling up internal combustion engine vehicles are small and do not compensate for the purchase price of an electric vehicle.
Keywords: electromobility; charging station; electric vehicle